STUDI EKSPERIMENTAL PENGGUNAAN SABUT KELAPA SEBAGAI SERAT PENGUAT KAMPAS REM NON ASBES - Mochammad Davi Yudha Prakasa; Dhimas wicaksono; Sehono Sehono (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2022)
One of the safety factors in a vehicle is the braking system, where the brakes are the biggest factor in slowing and stopping the vehicle and if neglected this brake system can cause accidents while driving which are quite fatal. Because the brakes bear of a crucial amount in the braking process or stopping a vehicle's speed. By utilizing waste coconut coir fiber to make brake linings with non-asbestos materials that have better mechanical properties. The specimens were made in 2 variations of fiber direction, namely vertical and horizontal fiber directions and each consisted of 3 specimens. And the specimen will be tested using the ogoshi method to find the specific wear value. The results showed that the level of wear of the brake pads with variations in the vertical direction had an average wear level of 4.78 × 10 -7 mm 2 /kg and variations in the direction of the horizontal fiber have an average wear rate of 3.37 × 10 -7 mm 2 /kg. So the conclusion of this study shows that the specific wear value can be influenced by differences in composition, as well as fiber direction. The direction of the fiber affects the difference in the specific wear value which is quite small, while the greater the content of coco fiber, the specific wear value is quite large and quite good compared to the specific wear value of the horizontal fiber direction. and the level of specific wear values of brake linings that are made not according to existing standards. which is where the standard value of the specific wear of the brake lining is 5 × 10 -4 mm 2 /kg up to 5 × 10 -3 mm2 / kg.